1988
DOI: 10.1093/jnci/80.9.626
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Methotrexate in Osteosarcoma

Abstract: High-dose methotrexate (MTX) is one of the agents currently used in intensive adjuvant chemotherapy regimens for nonmetastatic osteosarcoma. To elucidate the role of high-dose MTX in this disease, we present the history of trials conducted with MTX from the first single-agent studies through progressively complex combination regimens. With this background, some of the basic issues concerning MTX therapy in osteosarcoma are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…In the present study, we compared the growth inhibitory potential of PEDF with that of methotrexate, because methotrexate is one of the standard agents currently used in intensive adjuvant chemotherapy regimens for the patients with nonmetastatic osteosarcoma (Grem et al, 1998;Bacci et al, 1998). Methotrexate at the concentrations from 0.3 to 3 AM was reported to significantly inhibit the DNA synthesis in primary tumors derived from patients with osteosarcomas (Mordoh et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we compared the growth inhibitory potential of PEDF with that of methotrexate, because methotrexate is one of the standard agents currently used in intensive adjuvant chemotherapy regimens for the patients with nonmetastatic osteosarcoma (Grem et al, 1998;Bacci et al, 1998). Methotrexate at the concentrations from 0.3 to 3 AM was reported to significantly inhibit the DNA synthesis in primary tumors derived from patients with osteosarcomas (Mordoh et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…There is a considerable body of evidence supporting the role of high-dose methotrexate in the treatment of osteosarcoma since its first use in the 1970s, both as a single agent and as part of multiagent trials (Grem et al, 1988;Rosen, 1993). The advantages of adding high-dose methotrexate to an ifosfamide/etoposide combination include that, individually, it has an impressive single-agent profile; myelotoxic schedules can be resumed after only 1 week of administering HDMTX; and, properly administered, there is minimal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Ifosfamide and etoposide combinations have been evaluated previously in patients with recurrent paediatric sarcomas (Miser et al, 1987;Goorin et al, 1994;Tabone et al, 1994). High-dose methotrexate has evidence of activity both as a single agent and within multiple agent trials (Grem et al, 1988;Rosen, 1993). Of importance, high-dose methotrexate with folinic acid rescue can be given to neutropenic patients, thereby allowing another agent to be delivered during the myelosuppressive phase of the chemotherapy cycle and thus providing a degree of treatment intensification.…”
mentioning
confidence: 99%
“…The data reported in the current study indicate that late follow-up should also be reported, and that seasoned results may reflect an accurate appraisal of the true effects of treatment. 35 …”
Section: Discussionmentioning
confidence: 99%